Role of Genetics in Improving Fitness and Sports Performance - P. P. Ranganathan (Recent Trends in Sports, 2024)
Research indicates that variations in specific genes affects sports performance, comparing athletes with nonathletes. The genes that have been examined the most in relation to athletic performance are ACE and ACTN3. Strength and endurance have been associated with these genes, which also affect the type of fiber that makes up muscles. Sports performance factors primarily affected by genes are intrinsic motivation to exercise, power and endurance potential, training response to VO2 Max, exercise heart rate response, and exercise stroke volume. It also influences recovery and injury risk of performers. In addition to the aforementioned, genetics affects the tendency to cardio, glucose response of the body to cardio exercise, the response of the body composition to strength training, the utilization of protein, fat, and carbohydrates, the metabolism of caffeine, the response of cholesterol to dietary fat, the levels of polyunsaturated fatty acids, and the insulin response to dietary fat, HDL response to cardio, glucose response to cardio, insulin sensitivity response to cardio, testosterone levels, triglyceride response to cardio, vitamin utilization, and mineral utilization. Consequently, knowing these genetic impacts can offer athletes individualized insights for improving their diet and training plans.
Keywords: ACE gene; ACTN3 gene; Genetics; VO2 Max; insulin sensitivity; intrinsic motivation; triglyceride